Application of two intervention programs in order to optimize motivation and to improve eating habits in adult and elderly women - Leiton, Marta (2018)
The objective of this study was to analyse the effectiveness of two intervention programs: a physical exercise program with strategies to support the three basic psychological needs (autonomy, competence and relatedness); and a physical exercise program with nutritional education in order to improve the lifestyles of adult and elderly women who practiced functional maintenance. The Self-Determination Theory was applied as the theoretical framework. A sample of 135 women aged between 40 and 88 years (59.66 ± 10.76) who enrolled in a 12-week functional maintenance program and attended 24 exercise classes took part in the study. A quasi-experimental study was performed where strategies to support the three basic psychological needs were applied to one group and strategies for the improvement of eating habits were applied to the other group. No strategy was applied to the control group. The main results showed na improvement in experimental groups I and II when compared to the control group regarding the variables of autonomy, competence, intrinsic regulation, identified regulation, introjected regulation, external regulation and eating habits, after the application of the intervention programs. The conclusion is that both intervention programs were successful with this project's participants and that it is crucial to promote such intervention programs in functional maintenance classes, as they foster healthy lifestyles among participants.